HUBUNGAN REGULASI DIRI DENGAN KEPERCAYAAN DIRI ANAK USIA 5-6 TAHUN DI TK PERTIWI KECAMATAN BATANG PERANAP KABUPATEN INDRAGIRI HULU - Rini Sukma Yanti; Ria Novianti; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Thisstudy aimed to the correlation of self regulation and self confidence in Kindergartens pertiwi village batang peranap sub district indragiri hulu. The population in this study all children aged 5-6 years in Kindergartens pertiwi village batang peranap sub district indragiri hulu as many as 28 children from 2 classrooms. The tecnique of collecting data  is observation. The technique of data analysis is using product moment correlation technique with SPSS for windows version 17 program. Based on the result of the hypothesis test there is a significant positif between self regulation and self confidence on childern in 5-6 years in kindergartent pertiwi village batang peranap sub district indragiri hulu.This can be known from the value of the correlation coefficient of Rrx:0,504 and significance level 0,006<0,05. The level of correlation between self regulation and self confidencei included in the strong category being the value of determinant coefficient is equal to KD=×100% 25,4 % it means that self regulation  gives effect of 25,4% to self confidence. Key Word : Self Regulation- Self Confidence